Mentoring and Tutoring to Improve Student Learning Motivation in Kekait Village, West Lombok, after the Covid-19 Pandemic - Dian Islamiati; Syamsuddin, Syamsuddin; Kurniawidi, Dian Wijaya (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
Education in Indonesia encompasses all forms of education provided in Indonesia, both structured and unstructured. Education in Indonesia is divided into three main pathways: formal, non-formal, and informal. Education is also divided into four levels: early childhood, elementary, secondary, and higher education. Education is currently the foundation for the nation's development. Students, as the golden generation, are prepared for the future. Educators are the key to producing Indonesia's golden generation. Given that Indonesia has been hit by the COVID-19 pandemic in recent months, policymakers need to consider this when evaluating education in the new normal era. The purpose of this tutoring program is to optimize education in the regions during the new normal era. The method used is interactive learning between teachers and students, utilizing modules as learning resources and teacher guides. The program has resulted in several village children, from kindergarten to elementary school, receiving tutoring on school material they haven't yet mastered, particularly mathematics, English, and science. In this new normal era, it is important to hold tutoring programs for children because the learning time provided by schools is limited due to the ongoing pandemic.